1982
DOI: 10.1055/s-2008-1026072
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Prolonged Exercise Tests at the Individual Anaerobic Threshold and the Fixed Anaerobic Threshold of 4 mmol·l-1Lactate*

Abstract: Prolonged physical exercise tests (50 min) at the threshold of 4 mmol . l-1 lactate (ATc) and at the individual anaerobic threshold (IAT) were applied in 19 rowing athletes. In each of the rowers (n = 19) work loads corresponding to the IAT did not result in a gradual lactase accumulation or exhaustion within 50 min of exercise. Means of lactate concentration and heart rate at the end of exercise were 4.0 +/- 1.6 mmol . l-1 and 182 +/- 13.0 beats . min-1, respectively. In 15 of 19 rowers, the IAT corresponded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
122
0
8

Year Published

1983
1983
2000
2000

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 196 publications
(141 citation statements)
references
References 16 publications
11
122
0
8
Order By: Relevance
“…Original research showed that the workload at IAT was lower than the workload at OBLA in the majority of their trained participants, and since exercise was maintained for 50 min at the workload corresponding to the IAT but not OBLA, it was suggested that the IAT must be reflective of MLSS [159] , although multiple constant load tests were not performed. However, subsequent research showed that power output and blood [La -] reflective of IAT were significantly higher (12% and 68%, respectively; both p < 0.01) than MLSS power output and blood [La -] in trained male rowers (n = 9), despite there being a strong relationship between IAT power output and MLSS power output (r = 0.81; p < 0.01) [7] .…”
Section: Relationship and Agreement With Mlss And Performancementioning
confidence: 99%
See 4 more Smart Citations
“…Original research showed that the workload at IAT was lower than the workload at OBLA in the majority of their trained participants, and since exercise was maintained for 50 min at the workload corresponding to the IAT but not OBLA, it was suggested that the IAT must be reflective of MLSS [159] , although multiple constant load tests were not performed. However, subsequent research showed that power output and blood [La -] reflective of IAT were significantly higher (12% and 68%, respectively; both p < 0.01) than MLSS power output and blood [La -] in trained male rowers (n = 9), despite there being a strong relationship between IAT power output and MLSS power output (r = 0.81; p < 0.01) [7] .…”
Section: Relationship and Agreement With Mlss And Performancementioning
confidence: 99%
“…Amann et al [93] investigated the IAT determined via two methods; the traditional Stegmann and Kindermann method [159] and the modified version described above by Baldari and Guidetti [165] . It was found that the Baldari and Guidetti method (r = 0.72; p < 0.01) [165] but not the traditional Stegmann and Kindermann method (r = 0.52; p > 0.05) [159] was significantly correlated with 40 km cycling time trial performance in trained male cyclists (n = 15). However, power output determined by the Baldari and Guidetti method [165] significantly underestimated 40 km time trial power output (14%; p value not stated) and therefore its capacity to establish a performance intensity cannot be confirmed.…”
Section: Relationship and Agreement With Mlss And Performancementioning
confidence: 99%
See 3 more Smart Citations